2014
DOI: 10.3329/jemc.v4i3.20944
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study on 100 Patients with Polycystic Ovarian Syndrome (PCOS)

Abstract: Background: Women with polycystic ovarian syndrome (PCOS) have chronic anovulation and androgen excess not attributable to another cause. The fundamental pathophysiologic defect is unknown. Defects in LH secretion, LH/FSH ratio, amplitude of LH pulsations have been described; but the prevalence of these defects is not still clearly determined. Objective: To review the variable clinical presentations of polycystic ovarian syndrome. Materials and Methods: This observational study was carried out in Combined Mili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In our study, we found that LH/FSH changes were attribute of 23.3% of cases with PCOS and in 16.7% of controls, which differs from the findings of other studies, in which higher incidence was reported 29 . Moreover, our results show that obesity was not a risk factor for an abnormal LH/FSH ratio, disproving the traditional concept of the disease that the heavier the patient is, the higher the LH/FSH ratio, and our results agree with a recent report 43 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that LH/FSH changes were attribute of 23.3% of cases with PCOS and in 16.7% of controls, which differs from the findings of other studies, in which higher incidence was reported 29 . Moreover, our results show that obesity was not a risk factor for an abnormal LH/FSH ratio, disproving the traditional concept of the disease that the heavier the patient is, the higher the LH/FSH ratio, and our results agree with a recent report 43 .…”
Section: Discussionsupporting
confidence: 89%
“…17,18 Hirsutism was noted in 33.9% of women which was consistent with the findings published in literature of a few studies as 28% and 30%. 18,19 However, few studies have reported a higher incidence (64%) of hirsutism in women with PCOS. 17 Derangement in the gonadotrophin ratio (FSH/LH) occurs in PCOS due to discriminate increase in LH levels.…”
Section: Discussionmentioning
confidence: 99%